Community seed banks in Nepal past, present, future: Proceedings of a National Workshop, 14-15 June 2012, Pokhara, Nepal - Vernooy, Ronnie; Shrestha, P.; Chaudhary, P. (Bioversity International, 2013)
In Nepal, community seed banks have a long and rich history. Supported in particular by a number of non-government organizations and more recently, also by government agencies, they can be found across the country from the lowland terai to the high hill areas and from east to west. The latest count puts the number of active community seed banks at 115. These proceedings present the contributions of community seed banks to the conservation and sustainable use of agricultural biodiversity. The various contributions discuss conceptual, practical and policy issues concerning the establishment and management of community seed banks. Lessons learned from the experiences in Nepal will be useful for community seed banks globally.